The Effect of Education on Nutrition Knowledge and Function of Pregnant Women in Hamadan Health Centers - Fatemeh SHobeiri; Khadigeh Afshari; Maryam Farhadian (Hamadan University of Medical Sciences, 2018)
Introduction: Proper nutrition during pregnancy is very important. The purpose of this study was to determine the effect of education on knowledge and nutritional behavior of pregnant women referring to Hamadan health centers in 2016. Methods: The present study is a quasi-experimental study. 100 pregnant women referred to selected health centers of Hamadan who fit the criteria for entering the study, participated in the study after obtaining informed consent and were randomly assigned to intervention and control groups. In the experimental group, in addition to routine care, nutritional behaviors training was carried out in four sessions of 45-60 minutes in two weeks. The data collection tools were demographic information and nutritional behaviors questionnaire. The validity and reliability of the questionnaires were measured. In both groups, the questionnaires were completed before, immediately and 6 weeks after the intervention. Data analysis was performed using SPSS16 and descriptive and analytical statistics (independent and paired t-test, chi square and repeated measures analysis). Results: According to Chi-square test, there was no significant difference between the two groups in terms of age, occupation, education, BMI, sport, and family income, and were homogeneous. Before the intervention, the two groups were homogeneous in terms of the mean scores of components of Pender Health Promotion Model. After the intervention in the experimental group, the nutritional behavior scores and components of Pender Health Promotion Model increased significantly (P<0.001) compared to the control group. Conclusion: Results of this study showed that using the principled education based on the Pender Health Promotion Model, women's awareness of proper nutrition during pregnancy can be increased.